Selected models of speech perception by students 5 semester English Education Study Program Universitas Nias of english during lecturing - Harefa, Afore Tahir; Halawa, Mercy Dwiyul; Hulu, Delan Septiani; Telaumbanua, Enjel Tris Jelita (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Understanding speech (speech perception) is an important ability that English language students must master. There are several theoretical models of speech comprehension that attempt to explain the cognitive and linguistic processes underlying this ability. As for speech perception models, 1) Motor Theory of Speech Perception, 2) Analysis-by-Synthesis, 3) Group Model, 4) Fuzzy Logic Model, 5) TRACE Model. This study aims to find out what kind of speech perception model used by students in lectures, especially in the process of teaching and learning English. Specifically, this research is classified as qualitative research. To collect data, the participants studied were the 5th semester population of the English education study program, especially at Nias University. Random samples were used and the samples were 7 people from class A. From the results that have been obtained, there are 4 (four) students classified as using the Cohort model, 2 (two) students classified as using the Motor Theory model, and 1 (one) student classified as using the Fuzzy Logical Model, so we can conclude that most students use the Cohort model they often use this model in English learning activities every day.